2008
DOI: 10.1080/15574090903141104
|View full text |Cite
|
Sign up to set email alerts
|

Smoking It All Away: Influences of Stress, Negative Emotions, and Stigma on Lesbian Tobacco Use

Abstract: This study explored the reported processes, conditions, and consequences of lesbian and heterosexual female smoking and relapse to understand the reasons for elevated lesbian smoking rates. Using grounded theory techniques, we conducted semistructured, face-to-face interviews with an ethnically diverse sample of 35 lesbian and 35 heterosexual female participants in Northern California. We found minority stress/sexual stigma to be an additional, unique cause of negative emotions and stress reported by 75% of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…Among a probability-based sample of adolescent school students, Bontempo and D'Augelli (2002) found that lesbian, gay, and bisexual students' elevated risk behaviors, which included smoking, were attributable to at-school victimization, which was defined as having their property vandalized or being threatened or injured with a weapon in the past 12 months; discrimination was not assessed. Furthermore, at least two qualitative studies with sexual minorities reported emergent themes of stress management cited by participants as reasons for their smoking (Gruskin, Byrne, Altschuler, & Dibble, 2008;Remafedi, 2007), but quantitative investigations are needed to empirically investigate these associated risk factors.…”
Section: Associations Of Discrimination and Violence With Smoking Amomentioning
confidence: 99%
“…Among a probability-based sample of adolescent school students, Bontempo and D'Augelli (2002) found that lesbian, gay, and bisexual students' elevated risk behaviors, which included smoking, were attributable to at-school victimization, which was defined as having their property vandalized or being threatened or injured with a weapon in the past 12 months; discrimination was not assessed. Furthermore, at least two qualitative studies with sexual minorities reported emergent themes of stress management cited by participants as reasons for their smoking (Gruskin, Byrne, Altschuler, & Dibble, 2008;Remafedi, 2007), but quantitative investigations are needed to empirically investigate these associated risk factors.…”
Section: Associations Of Discrimination and Violence With Smoking Amomentioning
confidence: 99%
“…53 Research on stigma suggests that public health policies which purposefully use stigma to change behavior may have unintended consequences for groups who are already stigmatized in society by virtue of some other characteristic, like their sexual and/or gender identity. 14,45,54 For example, stigmatized people may experience a "diminished sense of self-esteem and self-efficacy" 55 that translates into fatalistic attitudes about one's ability to change.…”
mentioning
confidence: 99%
“…26 In addition to the same risk factors for smoking that confront other groups, sexual and gender minorities also face additional factors that exacerbate their risk, including social environments that are accepting of smoking, 27,36,37 aggressive targeting by the tobacco industry, [38][39][40][41][42] and perhaps most notably stigma-related processes including minority stress, psychological distress, and social isolation. 24,26,[29][30][31]39,[43][44][45][46][47][48][49] The alarmingly high risk of smoking among sexual and gender minorities together with research that has documented a relationship between stigma-related processes and smoking prevalence for these groups raises questions about whether tobacco-related stigma intensifies the disadvantages associated with the stigmas of other social identities. 47,50 Stigma research in public health has been criticized for too narrowly focusing on a singular stigmatizing attribute, and neglecting to recognize that stigmatized people often experience multiple forms of stigma.…”
mentioning
confidence: 99%
“…Previous research show that some sexual minority women see smoking as a way to deal with general and sexuality-related stressors. [22,34] Our analysis suggests that those who take up and those who continue smoking have fewer economic, social and psychological resources than women who never smoke. Future interventions may find utility focusing on personal resilience to deal with general and sexuality-specific stressors, ensuring that imagery and messaging don't alienate target audiences by using stereotypes, [35] and attending to accessibility issues.…”
Section: Discussionmentioning
confidence: 99%